On the Potential of 25 Years (1991–2015) of Rawinsonde Measurements for Elucidating Climatological and Spatiotemporal Patterns of Afternoon Boundary Layer Depths over the Contiguous US - Temple R. Lee; Sandip Pal (Advances in Meteorology)
The daytime planetary boundary layer (PBL) depth is an essential parameter in, for example, dispersion models and numerical weather prediction. We applied a recently developed technique to estimate afternoon PBL depths from 516,887 daily rawinsonde measurements obtained at 0000 UTC between 1 Jan 1991 and 31 Dec 2015 from 67 US sites. We discuss salient features in the PBL depth variability and examine the climatology of afternoon PBL depths as a function of geographical region and Köppen-Geiger climate regime. Results indicated a strong east to west PBL depth gradient, with higher PBL depths over the semiarid regions of the western US in spring and summer. Many sites located near coastlines exhibited no seasonal cycle due to marine boundary layer influences, and an inverse relationship was found between distance from the coast and observed afternoon PBL depth. Differentiating by climate type, BWk (arid, desert, and cold) has the largest median winter (1075 m) and summer (2500 m) PBL depths. Median PBL depths for Cfa (temperate, no dry season, and hot summers), Dfa (cold, no dry season, and warm summer), and Dfb (cold, no dry season, and hot summers) climate types are 750 m and 1000 m during winter and summer, respectively.